2020
DOI: 10.1124/jpet.120.000196
|View full text |Cite
|
Sign up to set email alerts
|

Prostanoid Receptors of the EP4-Subtype Mediate Gene Expression Changes in Human Airway Epithelial Cells with Potential Anti-Inflammatory Activity

Abstract: Running Head: Genomic effects of an EP 4-receptor agonist in human airway epithelia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…To examine the effects of PGE 2 on respiratory epithelial function, we cultured healthy human tracheal and sinus epithelium in the presence or absence of PGE 2 . Of the 4 PGE 2 receptors (EP1–4), EP4 and to a lesser extent EP2 are expressed in airway epithelial cells ( 26 ). We found that chronic exposure to PGE 2 progressively increased 3D organoid diameter in an EP4- but not EP2-dependent fashion ( Figure 5, A and B ), similar to effects reported in intestinal epithelium ( 27 , 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…To examine the effects of PGE 2 on respiratory epithelial function, we cultured healthy human tracheal and sinus epithelium in the presence or absence of PGE 2 . Of the 4 PGE 2 receptors (EP1–4), EP4 and to a lesser extent EP2 are expressed in airway epithelial cells ( 26 ). We found that chronic exposure to PGE 2 progressively increased 3D organoid diameter in an EP4- but not EP2-dependent fashion ( Figure 5, A and B ), similar to effects reported in intestinal epithelium ( 27 , 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…To examine the effects of PGE2 on respiratory epithelial function, we cultured healthy human tracheal and sinus epithelium in the presence or absence of PGE2. Of the four PGE2 receptors (EP1-4), EP4 and to a lesser extent EP2 are expressed in airway epithelial cells (26). We found that chronic exposure to PGE2 progressively increased 3D organoid diameter in an EP4- but not EP2-dependent fashion (Figure 5A-B), similar to effects reported in intestinal epithelium (27, 28).…”
Section: Resultsmentioning
confidence: 99%
“…A cAMP-dependent mechanism was also implied in BEAS-2B cells treated with the selective EP2and EP4-receptor agonists ONO-AE1-259 and ONO-AE1-329, respectively (Suzawa et al, 2000). These ligands promote canonical, cAMP-dependent signaling in human airway epithelial cells but are partial agonists (Joshi et al, 2021) and were, therefore, used in cells pre-treated with the PDE4 inhibitor, RNO (1 µM). Exposure of BEAS-2B cells to ONO-AE1-259 and ONO-AE1-329 (both 1 µM; 60 min) reduced basal pERK1/2 levels, which was blocked by the EP2and EP4-receptor antagonists TG4-155 (Jiang et al, 2012) and L-161,982 (Machwate et al, 2001), respectively (both 1 µM; 30 min pre-treatment) (Fig.…”
Section: β2-adrenoceptor Agonists Promoted Erk1/2 Dephosphorylation In Airway Epithelial Cells Bymentioning
confidence: 99%
“…They also posit that this "biased agonism" is mediated by β2-adrenoceptors located on airway epithelial cells. This is a credible proposal because the airway epithelium promotes and regulates inflammatory processes, is the first site of action for inhaled therapies and expresses a population of efficiently coupled β2-adrenoceptors (Davis et al, 1990;Joshi et al, 2021;Kelsen et al, 1995;Knight and Holgate, 2003;Penn et al, 1994). Moreover, extracellular signal-regulated kinases 1 and 2 (ERK1/2) are phosphorylated to a greater degree in bronchial biopsies taken from asthmatic subjects than in healthy controls, with changes in the airway epithelium being positively correlated with indices of inflammation (Alam and Gorska, 2011;Liu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%